Genomic and Metabolomic Analyses of Natural Products in Nodularia spumigena Isolated from a Shrimp Culture Pond - POPIN, Rafael Vicentini (Multidisciplinary Digital Publishing Institute, 2023)
The bloom-forming cyanobacterium Nodularia spumigena CENA596 encodes the biosynthetic gene clusters (BGCs) of the known natural products nodularins, spumigins, anabaenopeptins/namalides, aeruginosins, mycosporin-like amino acids, and scytonemin, along with the terpenoid geosmin. Targeted metabolomics confirmed the production of these metabolic compounds, except for the alkaloid scytonemin. Genome mining of N. spumigena CENA596 and its three closely related Nodularia strains—two planktonic strains from the Baltic Sea and one benthic strain from Japanese marine sediment—revealed that the number of BGCs in planktonic strains was higher than in benthic one. Geosmin—a volatile compound with unpleasant taste and odor—was unique to the Brazilian strain CENA596. Automatic annotation of the genomes using subsystems technology revealed a related number of coding sequences and functional roles. Orthologs from the Nodularia genomes are involved in the primary and secondary metabolisms. Phylogenomic analysis of N. spumigena CENA596 based on 120 conserved protein sequences positioned this strain close to the Baltic Nodularia. Phylogeny of the 16S rRNA genes separated the Brazilian CENA596 strain from those of the Baltic Sea, despite their high sequence identities (99% identity, 100% coverage). The comparative analysis among planktic Nodularia strains showed that their genomes were considerably similar despite their geographically distant origin.